Relações entre raios e chuvas na Amazônia Oriental - POMPEU, Marcela Machado (Universidade Federal do Pará, 2015)
The objective of this study was to analyze the relationship between electrical discharges of the atmosphere and the precipitation in selected areas of eastern Amazonia during the period of September 2008 to December 2010. These areas correspond to three target circles of similar latitudes and two river basins, all located in the eastern Amazon Region.The first type of studies were conducted within radii of 100 km,centered at rain gauges within the towns of Belém, Caxiuanã and Santarém. These areas were chosen because they are situated roughly the same latitudes but ,different distances from the Atlantic Ocean. The objective was to observe the seasonality of the precipitation systems which cause lightning and their penetration in the continent, to determine the different climatological characteristics of each area. Lightning data was obtained fron the STARNET siystem. The rainfall data were obtained from the database of the ANA, RPCH, INMET and through the LBA station in Caxiuanã. The large-scale weather systems accompanied by small scale systems, appear to act primarily in Belém and weaken as they propagate to the other areas of study.In Belém, it was a observed the highest occurrences of lightning compared to Caxiuanã and Santarem.The peaks of lightning occurrences Caxiuanã and Santarem, approximately two months .The effect of the north-south drif of the ITCZ and its coupling with other systems at local or meso scale was observed. Analysis was made of a case study in Belem and Santarem and it was show that in the ITCZ does not follow the same pattern for these theree areas. A second type of study consited in na aplication within the basins of the Tocantins and Xingu River through a pioneering study of the relationship between lightning and rainfall.It was an attempt to contribute to predict the periods of floods and droughts within these basins through electrical discharges data. The detailed study was conducted in the areas upstream of dams in the Tocantins area1 where the Tucuruí hydroelectric power plant was installed, and also within the area of the Xingu basin is being built where the Belo Monte dam rainfall data from-HIDROWEB ANA pluviometric station operated by CPRM in each study area, were and also obtained in these basins . Using moving average filtes applied to lightning and rainfall,it was observed that the best relationship between, these variables occurred within the basin of the Tocantins, probably because it has more rain fall stations than the Xingu.basin.Considering the fact that the data corresponding to only two years of observations does not provide enough statistical weight to establish permanent quantitative relationships between lighting occurrences and rainfall, the derived equations may be considered as preliminary results. Nevertheless it was well established that this methodological approach may be applied to subsidize estimates of precipitation over selected areas, as well as, contribute with information to hydrological models for river basins, especially where pluviometric data are data are scarce and need an alternative source of information, in eastern Amazonia.